Pleural Effusion in Children: How often do we suspect Tubercular origin? - Shrestha, PN; Rayamajhi, A (Journal of Nepal Paediatric Society, 2010)
Introduction: Pleural effusion is a common problem in children; mostly due to common causes like pyogenic or tubercular infections. Different studies have showed that about 30%-60% of pleural effusion have resulted into formation of empyema. Method: This was an observational study done in children aged 3 months to 14 years with a diagnosis of pleural effusion admitted at Kanti Children’s Hospital, Maharajgunj from August 2009 to March 2010. The aim of the study was done to find out different modalities of treatment for the same and their outcome. A detailed clinical history and physical examination, was done in all children. Chest x-ray, laboratory reports and treatment were recorded and all patients followed up until death or discharge. Any change of management was also noted. Pleural effusion caused by nephritic syndrome or congestive cardiac failure were excluded from the study. Results: During the study period of eight months, 64 patients were admitted with the diagnosis of pleural effusion. Boys to girls ratio was 2:1. Right-sided pleural effusions were more common than left sided pleural effusions (53% vs. 37%). Most of patients improved with parental antibiotics along with chest tube drainage (62%). One in three patients (31%) received anti-tubercular drugs. Three patients (4.6%) were referred to surgeon for decortications and one patient (1.6%) died. Conclusion: Though chest tube drainage with parental antibiotics was the mainstay of treatment of pleural effusion, however one-third of patients also received anti-tubercular drugs. Key words: Pleural effusion; pyogenic; decortication; adenosine deaminase (ADA). DOI: 10.3126/jnps.v30i3.3914 J Nep Paedtr Soc 2010;30(3):132-134 Introduction: Pleural effusion is a common problem in children; mostly due to common causes like pyogenic or tubercular infections. Different studies have showed that about 30%-60% of pleural effusion have resulted into formation of empyema. Method: This was an observational study done in children aged 3 months to 14 years with a diagnosis of pleural effusion admitted at Kanti Children’s Hospital, Maharajgunj from August 2009 to March 2010. The aim of the study was done to find out different modalities of treatment for the same and their outcome. A detailed clinical history and physical examination, was done in all children. Chest x-ray, laboratory reports and treatment were recorded and all patients followed up until death or discharge. Any change of management was also noted. Pleural effusion caused by nephritic syndrome or congestive cardiac failure were excluded from the study. Results: During the study period of eight months, 64 patients were admitted with the diagnosis of pleural effusion. Boys to girls ratio was 2:1. Right-sided pleural effusions were more common than left sided pleural effusions (53% vs. 37%). Most of patients improved with parental antibiotics along with chest tube drainage (62%). One in three patients (31%) received anti-tubercular drugs. Three patients (4.6%) were referred to surgeon for decortications and one patient (1.6%) died. Conclusion: Though chest tube drainage with parental antibiotics was the mainstay of treatment of pleural effusion, however one-third of patients also received anti- tubercular drugs. Key words: Pleural effusion, pyogenic, decortication, adenosine deaminase (ADA). DOI: 10.3126/jnps.v30i3.3914 J Nep Paedtr Soc 2010;30(3):132-134